Detection of BRCA-1 gene mutations in epithelial ovarian tumors at tertiary care hospital Karachi - Gul, Shaista; Muhammad Ishaque, Syed; Muhmmad Khosa, Shafi; Zafar, Shahid; Ali Khan, Ahmad; Jan Panezai, Abdullah (International Journal of Pathology, 2024)
ABSTRACT Background: Ovarian cancer is the most common and lethal gynecological malignancy. Ovarian malignancy is the 3rd most common cancer in Pakistan. More than 90% ovarian cancers are of epithelial cell origin, about 24-40% such cancers have hereditary or sporadic mutation in the BRCA-1 or BRCA-2 genes. The present study was designed to detect BRCA-1 gene mutations in different histological sub-types of epithelial origin of benign, borderline and malignant ovarian tumors. Methods: This cross-sectional study was based on the analysis of BRCA-1 gene mutations in the epithelial origin of benign, borderline and malignant ovarian tumors received at the department of Pathology, Basic Medical Sciences Institute, Jinnah Post graduate Medical Centre, from 01-01-2011 to 31-12-2015. A total of 80 diagnosed cases were selected and analyzed for PCR. Results: BRCA-1 gene mutations were detected in 22 (27.5%) cases out of the 80 randomly selected epithelial ovarian tumors. Serous cyst adenocarcinoma was the commonest including 63% cases. BRCA-1 gene mutations were also positive in other epithelial ovarian tumors, including Mucinous cyst adenocarcinoma (13.6%), Endometroid adenocarcinoma and Mixed Mullerian tumor (4.5% each). In addition mutations were also detected in borderline tumors including Mucinous borderline tumor (9.09%) and Seromucinous borderline tumors (4.5%).The observations and results of the study were elaborated with the assistance of tables, figures and photomicrographs. Conclusion: BRCA-1 gene mutations manifestations were identified in a large number of serous malignant ovarian tumor cases. Small percentages of borderline and malignant mucinous tumors, endometroid adenocarcinoma and mixed mullerian tumor were also positive for BRCA-1 gene mutations.